Issues of bibliographical periodicals of the period 1981-1985: analytical review - Janonis, Osvaldas (Knygotyra, 1990)
Thirty issues of various bibliographical periodicals (published in this republic) were analyzed based on their different features for the period of 1981-1985. The analysis of the methods used in these issues revealed some drawbacks. Recommendations for improving these methods are provided in the article.